School Discipline and Classroom Management in the Brazilian Educational Field - Rafael Rodrigues da Silva (Universidade Federal do Rio Grande do Sul, 2016)
The text aims to analyze aspects related to school discipline and classroom management as a research field and as professional matter. It starts with a brief review of the North American tradition of research on the topic. In the second part, I analyze potentials and limits associated with assuming school discipline and classroom management as a research field in Brazil, using as parameters the papers published in Brazilian academic events like ANPEd annual meetings between 2007 and 2011 and the seminar on Indiscipline in the Contemporary School. The third part approaches the relationship between classroom management, as professional knowledge, and teacher education in Brazil. The last part is devoted to the final remarks.